Legal environment and corporate finance: Evidence from the Italian manufacturing industry - Greta Falavigna; R. Ippoliti (Journal of Economic Structures, 2021)
Considering the Italian manufacturing industry between 2014 and 2016 (more than 250,000 observations), this technical note analyzes the relation between the courts' ability to enforce credit rights and the opportunity to finance business activities with trade credits instead of financial debts, delaying payments and decreasing the financial costs. According to our results, and considering mortgage foreclosure, if the time necessary to settle an insolvency case increases by 1000~days, we can expect an increase in operating debt between 3 and 11%, and a decrease of financial expenses between 3000 and 7000 Euro.
Keywords: G32; G33; 330; Corporate finance; Institutional inefficiency; Manufacturing industry